Post-cardiac ring insertion impact on oral and periodontal health: Review - Hari, Febria Desi Kriswulan; Indrawati, Dwi Wahyu (Science Midwifery, 2025)
Coronary stent insertion is a medical procedure that aims to enhance coronary heart disease patients' cardiac blood flow. However, some studies suggest that this procedure can affect the health of the oral cavity's soft tissues and periodontals. Side effects can be caused by physiological changes after medical procedures as well as the consumption of medications such as antiplatelets and anticoagulants prescribed after the insertion of the ring. The purpose of this study is to investigate how heart ring insertion affects the condition of the oral cavity's soft tissues and periodontal by analyzing the available research results. The method used in this study was a literature review from various sources that discussed changes in the state of the mouth following the placement of a heart ring. The results showed that patients after heart band insertion were more prone to disorders such as xerostomia (dry mouth), recurrent canker sores, oral candidiasis, as well as a higher chance of developing periodontal disorders, including gingivitis and periodontitis. The main factors that contribute to this condition are the side effects of medications taken regularly, changes in the body's immune response, as well as the connection between cardiovascular disease and periodontal disease that deteriorates the patient's general health. The conclusions of this review emphasize the importance of a multidisciplinary approach between cardiologists and dentists in monitoring the oral health of patients undergoing heart ring placement. Prevention and education about oral and dental health care need to be provided to minimize the risk of further complications.